1991
DOI: 10.1128/jcm.29.9.2043-2046.1991
|View full text |Cite
|
Sign up to set email alerts
|

A novel group A rotavirus G serotype: serological and genomic characterization of equine isolate FI23

Abstract: Equine rotavirus F123 was shown to be prototypic of a novel G serotype, provisionally G14, by crossneutralization and VP7 sequence determination. Although distinct, there are as few as six differing amino acid residues (92, 94, 96, 146, 147, and 221) in the VP7 antigenic regions of F123 and G3 rotaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…This suggests that, while heterotypic immunity is possible with a monovalent vaccine, it is likely to be delayed in onset compared to homotypic immunity. Currently, there is a multivalent vaccine available that aims to induce heterotypic immunity, however, of all the G genotypes in group A rotaviruses, the two G types most prevalent in horses, G3 and G14, are also the most genetically similar (Browning et al, 1991d), which raises questions about the benefit of using a multivalent vaccine in horses. Furthermore, studies on vaccination of dams with monovalent inactivated rotavirus vaccines have shown that the response generated is typically panserotypic, generating neutralising antibodies against rotavirus serotypes that are unlikely to have infected the dam previously (Browning et al, 1991b;.…”
Section: Immunity and Vaccinationmentioning
confidence: 99%
“…This suggests that, while heterotypic immunity is possible with a monovalent vaccine, it is likely to be delayed in onset compared to homotypic immunity. Currently, there is a multivalent vaccine available that aims to induce heterotypic immunity, however, of all the G genotypes in group A rotaviruses, the two G types most prevalent in horses, G3 and G14, are also the most genetically similar (Browning et al, 1991d), which raises questions about the benefit of using a multivalent vaccine in horses. Furthermore, studies on vaccination of dams with monovalent inactivated rotavirus vaccines have shown that the response generated is typically panserotypic, generating neutralising antibodies against rotavirus serotypes that are unlikely to have infected the dam previously (Browning et al, 1991b;.…”
Section: Immunity and Vaccinationmentioning
confidence: 99%
“…Serotypes 1 4 are the predominant strains, while serotypes 6, 8, 9, and 12 are minor causes of gastroenteritis in humans. Serotypes 5, 7, 10, 13, and 14 have not been reported in humans [Estes and Cohen, 1989;Browning et al, 1991;Gerna et al, 19921. Although neutralization tests (plaque reduction, tube neutralization, or fluorescent focus reduction) have been used for serotyping, these methods are cumbersome because viruses must first be cultured from stool samples. An enzyme immunoassay with monoclonal antibodies (EIA-MAb) has been developed to determine serotypes directly from stool samples [Taniguchi et al, 19871.…”
Section: Introductionmentioning
confidence: 99%
“…Rotavirus outer capsid proteins are composed of VP4 and VP7, which induce neutralising antibodies. At least eight serotypes of group A human rotaviruses (HRVs), serotypes 1, 2, 3,4, 6, 8, 9, and 12, have been described on the basis of cross-neutralisation studies with hyperimmune sera containing neutralising antibodies to both the VP7 and VP4 polypeptides [Estes and Cohen, 1989;Browning et al, 1991;Gerna et al, 19921. Enzyme immunoassay with monoclonal antibodies (EIA-MAbs) against VP7 has been developed to determine serotypes directly from stool samples and to conduct epidemiological surveys of circulating HRVs [Taniguchi et al, 1987;Akatani and Ikegami, 19871. EIA-MAbs against VP4 was developed recently [Coulson, 19931. Reverse transcription and polymerase chain reaction amplification (RT-PCR) for the determination of VP7 serotypes (G types) and VP4 serotypes (P types) at the genetic level have been described [Gouvea et al, 1990; 0 1994 WILEY-LISS, INC. Gentsch et al, 19921.…”
Section: Introductionmentioning
confidence: 99%